1981
DOI: 10.1111/j.1445-2197.1981.tb05985.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Second Degree Haemorrhoids by Injection, Rubber Band Ligation, Maximal Anal Dilatation, and Haemorrhoidectomy: A Prospective Clinical Trial

Abstract: One hundred and twenty patients with confirmed second degree haemorrhoids were randomly allocated to four treatment groups: injection, rubber band ligation, maximal anal dilatation, and haemorrhoidectomy. Each group consisted of 30 patients. All patients were regularly followed up for at least one year. Assessment at one year showed that haemorrhoidectomy “cured” the haemorrhoids in 29 out of 30 patients. Rubber band ligation relieved 25 out of 30 and maximal anal dilatation 24 out of 30. Injection was the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 7 publications
3
22
0
1
Order By: Relevance
“…These findings correlate well with those of Murie et al [14] and Bayer et al [28]. However, Cheng et al [26] reported that 96 % patients were cured at 1 year following hemorrhoidectomy compared with 83 % following RBL. Almost similar findings were observed by Steinberg [19] and MacRae and Mcleod [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings correlate well with those of Murie et al [14] and Bayer et al [28]. However, Cheng et al [26] reported that 96 % patients were cured at 1 year following hemorrhoidectomy compared with 83 % following RBL. Almost similar findings were observed by Steinberg [19] and MacRae and Mcleod [29].…”
Section: Discussionsupporting
confidence: 90%
“…Cheng et al [26] report that hemorrhoidectomy is good in curing the disease, but higher possibility of post-op pain, complications and longer hospital study would not justify its use in the treatment of second hemorrhoid. Lewis et al [27] are of view that RBL is cheaper alternative to hemorrhoidectomy and reduces the demand for beds and pressure on surgical waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…Anal stenosis is a rare long term complication due to excess loss of anal mucosa with particular procedure and subsequent healing causes different grades of anal stenosis. Cheng FC et al [11] found haemorrhoidectomy caused pain in all cases, anal stenosis in 2 out of 30 patients. But no patient in band ligation and sclerotherapy had similar complaints.…”
Section: Discussionmentioning
confidence: 92%
“…Rubber band ligation was painless in 5 patients and produced pain for more than 48hours in 15 patients. Cheng FC et al [11] found that, haemorrhoidectomy caused pain in all cases, band ligation was painless in 26 out of 30 patients. Shah et al [12] revealed significantly higher (p<0.001) proportion of patients with pain who underwent band ligation than whom underwent injection Sclerotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…This is in accordance with the observations made by Gagloo et al 8 Cheng et al reported that haemorrhoidectomy is very effective in curing haemorrhoids, but higher possibility of postoperative operative complications, longer hospital study and development of new surgical procedures reduced its use in the treatment of hemorrhoids. 12 Buchmann et al and Mortensan et al are of view that Lord's dilatation procedure is cheaper with reduced postoperative complications and demand for beds in hospital. 13,14 But some complications like fecal incontinence may be seen.…”
Section: Discussionmentioning
confidence: 99%